Multiple Critical Periods for Rapamycin Treatment to Correct Structural Defects in Tsc-1-Suppressed Brain - Cox, Rebecca L.; Calderon de Anda, Froylan; Mangoubi, Tomer; Yoshii, Akira (Frontiers in Molecular Neuroscience, 2018)
Tuberous sclerosis complex (TSC) is an autosomal dominant neurogenetic disorder affecting the brain and other vital organs. Neurological symptoms include epilepsy, intellectual disability, and autism. TSC is caused by a loss-of-function mutation in the TSC1 or TSC2 gene. These gene products form a protein complex and normally suppress mammalian target of rapamycin (mTOR) activity. mTOR inhibitors have been used to treat subependymal glioma (SEGA) that is a brain tumor characteristic of TSC. However, neuropathology of TSC also involves dysregulated cortical circuit formation including neuronal migration, axodendritic differentiation, and synapse formation. It is currently unknown to what extent mTOR signaling inhibitors correct an alteration in neuronal morphology that have already formed prior to the treatment. Here, we address the efficacy of rapamycin treatment on neuronal migration and dendrite formation. Using in utero electroporation, we suppressed Tsc1 expression in a fraction of neuronal progenitor cells during the fetal period. In embryonic brain slices, we found that more Tsc1-suppressed cells remained within the periventricular zone, and rapamycin treatment facilitated neuronal migration. Postnatally, Tsc1-suppressed pyramidal neurons showed more complex branching of basal dendrites and a higher spine density at postnatal day (P) 28. Aberrant arborization was normalized by rapamycin administration every other day between P1 and P13 but not P15 and P27. In contrast, abnormal spine maturation improved by rapamycin treatment between P15 and P27 but not P1 and P13. Our results indicate that there are multiple critical windows for correcting different aspects of structural abnormalities in TSC, and the responses depend on the stage of neuronal circuit formation. These data warrant a search for an additional therapeutic target to treat neurological symptoms of TSC.